Blocking of LFA‐1 enhances expansion of Th17 cells induced by human CD14+CD16++ nonclassical monocytes. Issue 5 (24th March 2015) - Traunecker, Emmanuel; Gardner, Rui; Fonseca, João Eurico; Polido‐Pereira, Joaquim; Seitz, Michael; Villiger, Peter M.; Iezzi, Giandomenica; Padovan, Elisabetta
<x xml:space="preserve">Abstract</x> Among human peripheral blood (PB) monocyte (Mo) subsets, the classical CD14++CD16− (cMo) and intermediate CD14++CD16+ (iMo) Mos are known to activate pathogenic Th17 responses, whereas the impact of nonclassical CD14+CD16++ Mo (nMo) on T‐cell activation has been largely neglected. The aim of this study was to obtain new mechanistic insights on the capacity of Mo subsets from healthy donors (HDs) to activate IL‐17+ T‐cell responses in vitro, and assess whether this function was maintained or lost in states of chronic inflammation. When cocultured with autologous CD4+ T cells in the absence of TLR‐2/NOD2 agonists, PB nMos from HDs were more efficient stimulators of IL‐17‐producing T cells, as compared to cMo. These results could not be explained by differences in Mo lifespan and cytokine profiles. Notably, however, the blocking of LFA‐1/ICAM‐1 interaction resulted in a significant increase in the percentage of IL‐17+ T cells expanded in nMo/T‐cell cocultures. As compared to HD, PB Mo subsets of patients with rheumatoid arthritis were hampered in their T‐cell stimulatory capacity. Our new insights highlight the role of Mo subsets in modulating inflammatory T‐cell responses and suggest that nMo could become a critical therapeutic target against IL‐17‐mediated inflammatory diseases.